Вариант истории Дон Жуана в украинской культуре (архетип Леси-Долорес в балете «Каменный властелин» Виталия Губаренко по драме Леси Украинки) - Кашаюк, Вікторія Миколаївна; Kashaiuk, Viktoriia (Czasopismo Akademii Pomorskiej w Słupsku, 2016)
Lesya Ukrainka created a version of Don Juan’s history in Ukrainian culture. The poet introduced in the drama the Dolores image who loves Don Juan. Dolores became a symbol of the Love archetype in the art work. Vitaly Hubarenko’s work in great academic ballet genre is one of best artistic interpretations of this drama. Ballet style is an allusion to S. Prokofiev’s style. Dolores image gets characteristic by genres of lullaby and prayer. Tenderness of character is embodied by penetrating sound of violins in the high register. The transformation of Love theme is shows us another facet of the Dolores personality who committed a self-sacrifice act for the sake of a loved one. Dolores in the ballet is represents the female essence of love as a creation, thus the term „Femin-personalism” is offered in this article. The understanding of the term is defined by analogy with the philosophy. P. Bowne, E. Mounier, N. Berdyaev and other thinkers have shown an archetype of personality as a person which has a divine source.
The version of Don Juan’s history in Ukrainian culture (Lesya-Dolores archetype in „The stone proprietor” ballet by Vitaly Hubarenko at Lesya Ukrainka’s drama)
Keywords: музичний дискурс; архетип; балет; драма; фемін-персоналізм; музыкальный дискурс; фемин-персонализм; musical discourse; archetype; ballet; drama; Femin-personalism; творчість Лесі Українки; Lesya Ukrainka's creative; творчість Віталія Губаренка; Vitaly Hubarenko’s creative; Дон Жуан; Don Juan